Originally Posted by
ticbol Substitution here means you express the value of one variable in terms of the other variable from one of the two equations. Say, get x in terms of y, from the 1st equation. Then substitute that into the the 2nd equation, thereby you will have an equation involving only one variable. Blah, blah, blah.
From the 1st equation, we get the value of x in terms of y,
x -2y = 4 ------(1)
x = 2y +4 ------(1a)
Then we substitute that into the 2nd equation,
2x -3y = 7 -----------(2)
2(2y +4) -3y = 7
4y +8 -3y = 7
4y -3y = 7 -8
y = -1 ---------***
Substitute that into, say, (1a), ----[you can substitute that into any of the (1), (1a), or (2) equations above.]
x = 2(-1) +4
x = -2 +4
x = 2 -----------***
Check those findings against the original equations (1) and (2),
x -2y = 4 --------(1)
2 -2(-1) =? 4
2 +2 =? 4
4 =? 4
Yes, so, OK.
2x -3y = 7 -----------(2)
2(2) -3(-1) = 7
4 +3 =? 7
7 =? 7
Yes, so, OK.
Therefore, x=2 and y = -1. -----------answer.